Cross-border migration process of Nepalese people to India - Kunwar, Laxman Singh (Nepal Population Journal, 2018)
There is unique historical, socio-economic and political relationship between Nepal and India. Nepal and India has open boarder and there is long history of people’s migration from one country to another by crossing the border. There is no need of any formal document documents (passport, visa) for people of both country in cross border migration process Therefore, this study is confined to analyze the factors associated with cross border migration process of Nepalese people to India. In total, 809 households were randomly selected from studied VDC Daijee of Kanchanpur district. Structured questionnaires were designed to collect the information. In study Daijee VDC of Kanchanpur, out of 809 households, 426 households were cross border migrants households (current and returned). Ancestor’s participation, information provided by friends, self-decision of migrants themselves and moving alone by crossing border were reported as main contributors in cross border migration process.